2015
DOI: 10.5301/jbm.5000158
|View full text |Cite
|
Sign up to set email alerts
|

CEA in Evaluation of Adnexal Mass: Retrospective Cohort Analysis and Review of the Literature

Abstract: The combination of the tumor markers CEA and Ca125 did not contribute significantly to the detection of malignant adnexal masses compared with Ca125 alone. As our results suggest that higher CEA levels could be useful in differentiating metastatic tumors from primary ovarian malignancy and in diagnosis of mucinous histology, this issue should be investigated in large, well-designed, prospective cohort trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…53 81 84 91 96-109 The combination of a more extended tumor marker profile, including the addition of carcinoembryonic antigen (CEA) and/or carbohydrate antigen (CA 19-9) to CA 125, is useful mainly for differentiating between metastatic tumors from the gastrointestinal tract or pancreas and primary ovarian malignancy. [110][111][112][113] Statements on tumor markers (Statements 7-12)…”
Section: Tumor Markersmentioning
confidence: 99%
“…53 81 84 91 96-109 The combination of a more extended tumor marker profile, including the addition of carcinoembryonic antigen (CEA) and/or carbohydrate antigen (CA 19-9) to CA 125, is useful mainly for differentiating between metastatic tumors from the gastrointestinal tract or pancreas and primary ovarian malignancy. [110][111][112][113] Statements on tumor markers (Statements 7-12)…”
Section: Tumor Markersmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) is one of the longest known tumor antigens [27], and at present is still the most widely used tumor marker in the management of colorectal cancer [28, 29]. Elevated serum levels of this assay were demonstrated in patients with ovarian adenocarcinomas, up to 87–88% in mucinous histotypes [30]. Elevation of preoperative serum CEA was also strongly correlated with advanced stage in patients with primary MOC and most likely indicated a poor prognosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…The glycoprotein, with a half-life of approximately 7 days, was found to be expressed in gastrointestinal and mucosal tissue during fetal development but only minimally expressed in adult tissue (15,16). Further studies showed that it was also overexpressed in adenocarcinomas of varying origin including gastric, hepatic, lung, pancreatic, ovarian and prostate (17)(18)(19)(20)(21)(22)(23)(24). In colon cancer, the specificity and sensitivity of CEA has been shown to vary with advancing tumor stage, with specificity ranging between 37% and 86% in advanced disease, providing a useful means of monitoring disease (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%